Deep ultraviolet emission from multiple quantum wells on flat N-polar AlN templates fabricated using periodical pulsed H2 etching. (10th November 2021) - Okada, Narihito; Sakamoto, Ryota; Ataka, Kazuya; Ito, Tadatoshi; Matsumura, Wataru; You, Lu; Yao, Yongzhao; Ishikawa, Yukari; Tadatomo, Kazuyuki
Abstract: In a previous study, we successfully grew flat N-polar AlN layers on a c -plane sapphire substrate with a misorientation angle of 2.0° by metal-organic vapor phase epitaxy. However, its surface had undulations due to step bunching, and therefore further improvement of the surface flatness is required. In this study, we employed pulsed H2 etching during the growth of N-polar AlN layers to improve the surface flatness. Atomic force microscopy results indicated that the surface flatness was significantly improved, exhibiting a root mean square value of 0.4 nm. Further, the deep ultraviolet emission from AlGaN-based multiple quantum wells (MQWs) on the N-polar AlN layers was characterized, and the effect of the surface flatness on the optical characteristics was investigated. The surface flatness was found to play a crucial role in improving the optical characteristics of MQWs on N-polar AlN layers.